The Effect of Transaction Security and Influencer Credibility on the Trust of Generation Z Consumers in Live Commerce on Startup E-Commerce - Saiyidatul Kamalia Saudah; Rizki Febri Eka Pradani (Anjasmoro: Islamic Interdisciplinary Journal, 2026)
The rapid growth of live commerce in Indonesia presents both significant opportunities and challenges, particularly regarding the trust of Generation Z consumers. This study aims to analyze the effect of transaction security and influencer credibility on the trust of Gen Z consumers in live commerce on startup e-commerce platforms. A quantitative approach was employed using a survey method with a four-point Likert scale questionnaire distributed to 271 students of the Faculty of Social Sciences and Humanities, Universitas Nurul Jadid, Paiton Probolinggo, who belong to Generation Z and have used live commerce. Data were analyzed using multiple linear regression with SPSS version 27. The results indicate that: (1) transaction security has a positive and significant effect on Gen Z consumer trust (t-value = 3.939 > t-table = 1.969; sig. < 0.001); (2) influencer credibility has a positive and significant effect on Gen Z consumer trust (t-value = 17.387 > t-table = 1.969; sig. < 0.001); and (3) both variables simultaneously have a significant effect (F-value = 497.665 > F-table = 3.03; sig. < 0.001). The coefficient of determination (R²) of 78.8% indicates that both variables substantially explain the variation in Gen Z consumer trust. These findings imply that startup e-commerce platforms need to simultaneously strengthen transaction security systems and select highly credible influencers to enhance consumer trust in the live commerce ecosystem.